Speed control of a dc servomotor using analogue controller / Azlim Pet - Pet, Azlim (1999)
This thesis presents the design of an analogue speed controller for a de servomotor with unknown transfer function. The transfer function is obtained experimentally, using frequency response techniques. An approximate expression for the transfer function is obtained from the graphtcal plot of the experimental data. Then the Root Locus technique is used to design a controller to meet the given specifications Simulation of the compensated system using MATLAB shows that it is stable. It has a satisfactory transient response and it improves steady state error.